Incidence, Treatment, and Survival of Patients With T-Cell Lymphoma, T-Cell Large Granular Leukemia, and Concomitant Plasma Cell Dyscrasias - Braunstein, Zachary; McLaughlin, Eric; Ruiz, Miguel; Wei, Lai; Bumma, Naresh; Benson, Don; Devarakonda, Srinivas; Chaudhry, Maria; Khan, Abdullah; Cottini, Francesca; Hanel, Walter; Baiocchi, Robert; et al. (Frontiers in Oncology, 2022)
T-Cell malignancies are a group of heterogeneous disorders composed of primary cutaneous T-cell lymphomas (CTCLs), peripheral T-cell lymphomas (PTCLs), and T-cell leukemias, including T-cell large granular lymphocytic leukemia (T-LGLL). Cases of patients with combined T-cell malignancies and plasma cell dyscrasias (PCD) are reported in the literature, but these are mostly limited to case reports or small case series with <10 patients. Here, we described the clinical course of 26 patients and report baseline characteristics and clinical outcomes including overall survival (OS), progression-free survival (PFS), and objective response rates (ORRs) in this unique population. There was no survival difference in patients with CTCL or T-LGLL and concomitant PCD when treated with standard therapy directed at the T-cell malignancy when compared to historical controls. However, patients with PTCL and concomitant PCD had significantly inferior outcomes with rapid progression and worse OS and PFS at 1.7 years (p=0.006) and 4.8 months (p=0.08), respectively, when compared to historical controls for patients with PTCL, although the limited number of patients included in this analysis precludes drawing definitive conclusions. Treatment directed at the T-cell malignancy resulted in the eradication of the PCD clone in multiple patients (15.4%) including one with multiple myeloma (MM) who experienced a complete response after starting therapy directed at the T-cell malignancy. For patients with T-cell malignancies and concomitant PCD, treatment with standard T-cell-directed therapies is recommended based on this analysis with continued follow-up and monitoring of the concomitant PCD. Further studies are needed to definitively elucidate the increased risk of relapse in patients with PTCL and concomitant PCD, and larger, multi-center cohorts are needed to validate these findings across T-cell malignancies and PCDs.